2011
DOI: 10.1074/jbc.m111.246470
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory β-Glucan from Lentinus edodes Activates Mitogen-activated Protein Kinases and Nuclear Factor-κB in Murine RAW 264.7 Macrophages

Abstract: Lentinan, a cell wall ␤-glucan from the fruiting bodies of Lentinus edodes, is well known to be a biological defense modifier, but the signal transduction pathway(s) induced by Lentinan have not been elucidated. In this study, we extracted Lentinan (LNT-S) by ultrasonication from Lentinus edodes and report that, in murine RAW 264.7 macrophages, LNT-S glucan activated NF-B p65 and triggered its nuclear translocation as determined by Western blotting. Moreover, LNT-S enhanced NF-B-luciferase activity in the Dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…and its transactivation activity but without production of NO and TNF-␣ in RAW 264.7 macrophages, which was reported in our very recent work (38). When it co-stimulates RAW 264.7 cells with LPS, LNT-S shows completely different immunomodulatory behavior, that is, it did not augment the activation of ERK1/2 and JNK1/2 (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…and its transactivation activity but without production of NO and TNF-␣ in RAW 264.7 macrophages, which was reported in our very recent work (38). When it co-stimulates RAW 264.7 cells with LPS, LNT-S shows completely different immunomodulatory behavior, that is, it did not augment the activation of ERK1/2 and JNK1/2 (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Sample-LNT used in this study was extracted from the fruiting bodies of Lentinus edodes according to the previously described procedures (38), which was coded as LNT-S. LNT-S was dissolved in PBS and sterilized at 121°C for 20 min before use.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo fungal β-glucans mostly elicit anti-inflammatory, anti-oxidant and anti-tumour effects [25]. Lentinan from shiitake can regulate MAP kinases JNK1/2 and ERK1/2 and enhance the nuclear translocation of NF-κB but without NO and TNF-α production in RAW 264.7 cells [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…The purpose of our experiments was to identify a polysaccharide with immunomodulatory activity and decreased pro-inflammatory activity to reduce the side-effects of chemotherapy. Many studies have suggested that LNT can be used as an immune modulator to activate the production of various cytokines by macrophages (10,31). In the present study, we isolated BMDMs from BM tissue to examine the mechanism of action of LNT in regulating myelosuppression after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%